Experimental Study on Antivibration Control of Electrical Power Steering Systems - Zhaojian Wang; Hamid Reza Karimi (Journal of Applied Mathematics)
We focus on the antivibration controller design problem for electrical power steering (EPS) systems. The EPS system has significant advantages over the traditional hydraulic steering system. However, the improper motor controller design would lead to the steering wheel vibration. Therefore, it is necessary to investigate the antivibration control strategy. For the implementation study, we also present the motor driver design and the software design which is used to monitor the sensors and the control signal. Based on the investigation on the regular assistant algorithm, we summarize the difficulties and problems encountered by the regular algorithm. After that, in order to improve the performance of antivibration and the human-like steering feeling, we propose a new assistant strategy for the EPS. The experiment results of the bench test illustrate the effectiveness and flexibility of the proposed control strategy. Compared with the regular controller, the proposed antivibration control reduces the vibration of the steering wheel a lot.